Green engineering of Hong Kong and China's first data centre certified to LEED-CS 2009 Platinum. Issue 1 (2nd January 2018) - Cochrane, Helen; Leong, Fredrick; So, Steven; Or, George; Lai, Melvyn
ABSTRACT: This paper showcases the green engineering excellence in design, construction and operation of NTT Communications Hong Kong Financial Data Center Tower 2 (FDC2) at No. 6 Chun Kwong Street in Tseung Kwan O Industrial Estate, Hong Kong, and its roadmap in achieving LEED 2009 for Core and Shell Development (LEED-CS 2009) certification to the highest Platinum level. Key environmental issues are discussed with the adopted approach and technologies to avoid, minimise and mitigate environmental impacts. In particular, based on LEED assessment, FDC2 demonstrates the excellence in energy efficiency using server virtualisation to a significant reduction of ∼60% consumption equivalent to ∼510, 000, 000 kWh per year and greenhouse gas emission equivalent to 357, 000 tonnes of CO2 . This has attained the maximum 21 Points under LEED-CS 2009 EAc1 Optimise Energy Performance. Notably, FDC2 strives for "Think Sustainability from the Project Start" to reduce energy use, carbon footprint and environmental impacts, with achieving various firsts in Hong Kong and China (according to Green Business Certification Inc. (GBCI)). The sustainable operation of this world class green data centre will continue its pioneered, innovative and excellent environmental performance to play as a role model of sustainable development in the data centre and IT industry.